Developing STEM-based TGT learning model to improve students' process skills - Faizah Firdaus; Wachju Subchan; Erlia Narulita (JPBI (Jurnal Pendidikan Biologi Indonesia), 2020)
Strengthening STEM-oriented learning is necessary for 21st century, so the development of appropriate learning models must be carried out. The aimed to of this study were analized validity, effectiveness, and practicality of STEM-based Team Games and Tournament (TGT) learning model towards the students' science process skills. This research was research and development (R&D) with a 4-D development namely; Defining, Designing, Developing, and Disseminating. The study involved 2 experts as validators, 2 teachers as user, and 112 students in small-scale tests, large-scale tests, and distribution tests in SMA. The research was done until the stage of disseminating and produced. The results showed the validity value of 83% was categorized as very valid, the effectiveness score of 83.9% was categorized as good, and the practicality score was 87.5%, so that it was declared valid, effective, and practical to improve the science process skills. Therefore, it is recommended to be applied in schools.